A CRITICAL REVIEW OF THE IMPACT OF MULTINATIONAL CORPORATIONS (MNCS) ON INDONESIAN ECONOMY - Rizki Hegia Sampurna (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
Multinational Corporations (MNCs) undoubtedly have an important contribution to the development of national economy of a particular country. Indonesia is not without exception. Nevertheless, many experts are critical on the negative effects brought by MNCs. This study is set to survey the extant literatures on the impact of FDI/MNCs on Indonesian economy. Based on the critical review of these literatures, the study suggets that MNCs might bring both favorable and unfavorable impacts on the national economy of Indonesia. The economic spillovers, technology transfer, and boosting trade performance are mostly higlighted favorable impacts. The involvement of MNCs in the country’s economy is considered to be an easy way or short-cut for the government to engineer economic growth. On the other hand, MNCs are also considered harmful to the country’s economy. Some of mostly highlighted negative impacts of MNCs are creating dependent development, limited technology transfer, labor exploitation, encouraging government collusive practices, and environmental damage.